Group role play case: Designing a multiple sting, digitally focussed, marketing communications campaign plan for Cirque du Soleil’s next London show. (Journal of Applied Learning and Teaching, 2021)
Drawing on the magic of Cirque du Soleil, this armchair case study invites you to make an imaginary step into the world of digital advertising agencies. Flexing your communication skills and applying your marketing knowledge, this real world, hands-on activity challenges you to collaborate together to create a digitally focussed campaign that addresses the author-developed client brief. This case is designed for use in digital marketing and marketing communication (marcom) modules on both undergraduate and postgraduate programmes.